AB1119 Clinical, therapeutic characterisation and time to achive remission analysis of a colombian cohort with juvenile idiopathic myopathy. (12th June 2018) - Fuentes, R.; Cañola, M.; Diaz-Coronado, J.C.; Rojas-Villarraga, A.; Hernandez-Parra, D.; Perez-Estrada, P.; Salazar-Uribe, J.C.; Pineda-Tamayo, R.
Abstract : Background: The clinical characteristics of paediatric patients with idiopathic inflammatory myopathies difere from adutls in several aspects. Its clinical presentation can include amyopathic onset and the skin involvement has diferent charecteristics Objectives: To describe a Colombian cohort with Juvenile Myositis (JM) recruited in a rheumatology facility. Methods: A cross-section retrospective research with data collected between 2014 and 2017 from a population diagnosed before 16 years of age with Idiopathic Myopathy according to Peter and Bohan criteria and followed up for at least six months. Kaplan-Meier curves were performed to analize time to achieve remission. Results: Out of 37 patients, one was excluded for having a dystrophy myopathy gene, 73% fulfilled definitive and 16% probable Bohan and Peter criteria; most patients were female 75, 8%, 28 with mean age of onset 7, 2 years, and clinical remission was achieved on average at 4 years of disease. There was high prevalence of Gottron's sign and papules (89%), Heliotrope rash (62%) and Calcinosis (37%). Other involvements are described in Table 1. Antinuclear antibodies were positive in 52%. Electromyography (EMG) was positive for myopathy in 39% of the patients. Biopsy was compatible with myopathy in 10% and was negative in 32% of the patients. The most common treatment was metrothexate (91%) followed by antimalarials (72%) and corticoids (56, 7%). Medication used in severe forms included Cyclophosphamide (5%), Rituximab (16%) and IV Immunoglobulin (5%). Kaplan-Meier curves showed an earlier time to remmision in patients with Gottron sign compared to patients without them (HR:8, 25 HR CI95%IL:1, 076–63, 3;p=0042 and in childrens younger than 15 years compared to older patients (HR: 2, 529 HR95%IL: 1, 084–5, 901, p: 0, 039). Conclusions: Our results agreed with those obtained in other multi-centred studies including latin america that evaluated clinical and therapeutic characteristics in children with myopathy, Gottron's sign and papules being the most common findings and with high rates of calcinosis and joint involvement. There was a significant difference between remission lapse in patients younger than 15 years compared to older ones. Reference: [1], D. Guseinova, et al. Comparison of clinical features and drug therapies among European and Latin American patients with juvenile dermatomyositis. Clinical and Experimental Rheumatology2011; 29: 117–124 Disclosure of Interest: None declared